Unsteady Flow near the Junction Zone of Three Liquids - Joseph Abdulahad; Rutayna Eisa (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we consider the motion near the junction zone of three approximately plane liquid films of semi–infinite extent in two dimensional polar coordinate system with negligible inertia. We use Stokes equation to describe such flow. The pressure in the region of large curvature is less than that on the surface of bulk fluid and this pressure gradient ensures that this problem is unsteady state case. The equation that governs such flow is solved analytically, the shape and the thickness are determined for some liquids.